2018
DOI: 10.4049/jimmunol.1800732
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis B Virus Surface Antigen Enhances the Sensitivity of Hepatocytes to Fas-Mediated Apoptosis via Suppression of AKT Phosphorylation

Abstract: The Fas receptor/ligand system plays a prominent role in hepatic apoptosis and hepatocyte death. Although hepatitis B virus (HBV) surface Ag (HBsAg) is the most abundant HBV protein in the liver and peripheral blood of patients with chronic HBV infection, its role in Fas-mediated hepatocyte apoptosis has not been disclosed. In this study, we report that HBsAg sensitizes HepG2 cells to agonistic anti-Fas Ab CH11-induced apoptosis through increasing the formation of SDS-stable Fas aggregation and procaspase-8 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…In this pathway, death signals are transmitted via cell surface receptors that communicate with the FasL/Fas signaling pathway, which is part of the death receptor pathway. After binding to FasL, Fas trimerizes and interacts with Fas-associated protein with a death domain, which contributes to the cleavage of caspase-8 and caspase-10 and leads to activation of downstream effector caspases, including caspase-3, caspase-6 and caspase-7, ultimately causing apoptosis[24]. In this study, we demonstrated that QFGs treatment upregulated FasL and Fas protein expression.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In this pathway, death signals are transmitted via cell surface receptors that communicate with the FasL/Fas signaling pathway, which is part of the death receptor pathway. After binding to FasL, Fas trimerizes and interacts with Fas-associated protein with a death domain, which contributes to the cleavage of caspase-8 and caspase-10 and leads to activation of downstream effector caspases, including caspase-3, caspase-6 and caspase-7, ultimately causing apoptosis[24]. In this study, we demonstrated that QFGs treatment upregulated FasL and Fas protein expression.…”
Section: Discussionmentioning
confidence: 63%
“…In a previous study, overexpression of this complex has been found to induce cell proliferation, whereas p21 inhibited the effect of the cyclin D1/CDK4 complex[14]. During the regulation of cell apoptosis, Bax and Bcl-2 regulate the mitochondria-dependent pathway[21], while Fas and FasL activate the death receptor-mediated pathway[24]. We found that QFGs can inhibit proliferation via arrest of the cell cycle in HCT-116 and HCT-8 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fas-induced apoptosis has been proposed to function in various liver diseases, such as ischemia/reperfusion injury, viral hepatitis, fulminant hepatic liver failure, and nonalcoholic and alcoholic steatohepatitis [34,35,36,37]. Previous research suggested that s-glutathionylation of Fas results in robust Fas activation, which activates FasL-induced signaling and apoptosis [16,38].…”
Section: Discussionmentioning
confidence: 99%